Case report: Aumolertinib plus gumarontinib in a patient with EGFR mutated non-small-cell lung cancer harboring acquired MET amplification following progression on afatinib plus crizotinib - Hui, Jia-Jun; Ding, Sheng-Jun; Qin, Bao-Dong; Ding, Ning (Frontiers in Pharmacology, 2025)
BackgroundAlthough it remained fully unclear about the optimal regimen for Epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) resistant non-small cell lung cancer (NSCLC) patients with Mesenchymal-Epithelial Transition factor (MET) amplification, the dual inhibition of EGFR inhibitor with MET inhibitor were attempted in clinical practice. There is very limited literature on the subsequent treatment when patients develop the resistance to this combination regimen.Case summaryThe patient, a 49-year-old female, initially presented with EGFR exon 21 L858R metastatic lung adenocarcinoma, treated successfully with first-line afatinib on September 2022 with a progression-free survival (PFS) of 8.0 months. On May 2023, she developed chest tightness and was found to have pericardial and pleural effusions containing malignant cells, indicating disease progression. Next-generation sequencing using pericardial effusion revealed concurrent EGFR L858R mutation and MET amplification. Then, afatinib plus crizotinib was initiated as second-line regimen, achieving stable disease with a PFS of 13.5 months. On July 2024, the patient developed the resistance to afatinib plus crizotinib due to the appearance of brain metastases. Then, this patient was administrated with aumolertinib plus gumarontinib as third-line regimen. Remarkably, this led to significant radiographic improvement of brain metastases. This patient is still undergoing third-line treatment, with a PFS of 3.7 months.ConclusionThis case underscores the importance of re-challenge using third-generation EGFR-TKI with novel MET-TKI after the failure of second-generation EGFR-TKI plus crizotinib in EGFR-TKI resistant NSCLC patients with MET amplification, especially in patients with brain metastases. The successful application of aumolertinib plus gumarontinib highlights its potential in overcoming MET amplification-induced EGFR-TKI resistance, which warrants further investigation in future large-scale clinical trials.